2019
DOI: 10.7567/1347-4065/ab34fd
|View full text |Cite
|
Sign up to set email alerts
|

Relation between crystallinity and constituent distribution of an IGZO thin film

Abstract: This study examines the crystallinities of indium-gallium-zinc oxide (IGZO) films deposited by sputtering at room temperature under varying conditions and a difference in composition among the films, then we assess the effect of these differences on the FET characteristics. Each sample is found to be nanocrystalline IGZO. The crystallinity and the degree of the c-axis alignment are improved with the increase of the O 2 gas flow ratio in the IGZO deposition. The composition analysis results demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…This weak signature is attributed to a-IGZO , based as well on simulated XRD . Note that previous reports have observed that such a-IGZO can present a certain compositional ordering at the nanoscale, , but this is not resolved in the present study. The increase of T sub to 100 °C triggers, on the one hand, a shift of the weak diffraction maximum (WD max) to the left, and on the other hand, an appearance of a crystalline peak at 2θ = 35°.…”
Section: Resultscontrasting
confidence: 40%
See 3 more Smart Citations
“…This weak signature is attributed to a-IGZO , based as well on simulated XRD . Note that previous reports have observed that such a-IGZO can present a certain compositional ordering at the nanoscale, , but this is not resolved in the present study. The increase of T sub to 100 °C triggers, on the one hand, a shift of the weak diffraction maximum (WD max) to the left, and on the other hand, an appearance of a crystalline peak at 2θ = 35°.…”
Section: Resultscontrasting
confidence: 40%
“…Substrate temperature T sub and the O 2 flow ratio in the O 2 + Ar sputtering gas mixture ( R O 2 ) are the most studied sputtering parameters for tuning of IGZO TFT performance. T sub is typically set in a range from 25 to 300 °C for IGZO sputtering. , R O 2 can be varied from 0 to 100% and affects the electronic defect density correlated with oxygen in IGZO films. IGZO TFT electrical properties, including bias stress, are largely influenced by the oxygen concentration and binding state in the films, hence the optimization of R O 2 is essential for the development of IGZO TFTs with high bias stress stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, CAAC-OS FETs have the advantage of exhibiting an extremely low off-state current, making them suitable for display applications. Figure 2A indicates that even when the channel length of the [11][12][13][14][15][16][17][18][19][20] CAAC-OS FET employed as a driving FET is scaleddown to 200 nm, the off-state current remained lower than 1 × 10 −12 A, which is below the measurement limit. Therefore, when the display shows black, the amount of electric current that flows would be extremely small, leading to a low-power consumption.…”
Section: Properties Of Caac-os Fetmentioning
confidence: 99%